Staphylococcal mastitis in dairy cows - Kerro Dego, Oudessa; Vidlund, Jessica (Frontiers in Veterinary Science, 2024)
Bovine mastitis is one of the most common diseases of dairy cattle. Even though different infectious microorganisms and mechanical injury can cause mastitis bacteria are the most common cause of mastitis in dairy cows. Staphylococci, streptococci, and coliforms are the most frequently diagnosed etiological agents of mastitis in dairy cows. Staphylococci that cause mastitis are broadly divided into Staphylococcus aureus and non-aureus staphylococci (NAS). The NAS comprises mainly coagulasenegative Staphylococcus species (CNS) and some coagulase-positive and coagulase-variable staphylococci and. Current staphylococcal mastitis control measures are ineffective and dependence on antimicrobial drugs is not sustainable because of low cure rate with antimicrobial treatment and the development of resistance. Non-antimicrobial effective and sustainable control tools are critically needed. This review is a concise description of the current status of S. aureus and NAS mastitis in dairy cows and highlights areas of knowledge gaps.